Solid Phase Extraction and Flame Atomic Absorption Spectrometry for the Determination of Gold - Li, Hongwei; Huang, Zhangjie; Li, Weiqun (Asian Journal of Chemistry, 2012)
A solid phase extraction and flame atomic absorption spectrometry for the determination of gold with SEPABEADS SP207 resin as sorbent was studied. The formation of gold complex with 4-rhodanineazo benzoic acid (4-BARA) was preconcentrated on a nonpolar resin SEPABEADS SP207 and pentyl alcohol was used as eluent. The effects of various parameters such as acidity, flow rate of sample, type of eluent, amount of adsorbent and interfering ions have been studied. The gold in 250 mL solution can be concentrated to 5 mL, representing an enrichment factor of 50 was achieved. In the original sample detection limit was 0.3 μg L-1 using flame atomic absorption spectrometry. The relative standard deviation for eleven replicate measurements of 15 μg L-1 gold was 3.3 %. The method was applied to the determination of trace amount gold in ore samples with good results.